Identity Of The Hoa In Ho Chi Minh City Under Government Policies Since Immigration (Journal of Namibian Studies : History Politics Culture, 2023)
Due to varied reasons, the Chinese left their homeland migrating to Vietnam, espescially to Ho Chi Minh City. Since immigrated in different times, the Chinese diaspora in Ho Chi Minh City identified themselves differently through the years. This identity has been affected by not only the the mentality of immigrants but local government policies as well.Residing in new land, the Hoa had their social life situation changed gradually. With the hope that all things go back to their source eventually, Chinese immigrants first identified themselves as expatriates. They believed that someday, when homeland became peaceful and their life got better, they would return home. However, situation of economy, politics and society of both local region and homeland changed their mind. Chinese diaspora then turned to be a “half expatriate – half citizen”, and finally they identified themselves and publicly admitted as Vietnamese citizens. The changes in local government policies are main factors which directly influenced identity of the Hoa in Ho Chi Minh City.